PENGGUNAAN MEDIA PERPUSTAKAAN DALAM MENINGKATKAN MOTIVASI BELAJAR - Meilany Muskita, sherly (Widya Warta, 2016)
This research aims to find the influence of library media usage on students’ motivation to study. The population is the students of Guidance and Counseling Department, Catholic University of Widya Mandala Madiun in the academic year 2013/2014. The sample was taken employing incidental sampling technique. For the hypothesis testing, an analysis was conducted using statistical formulas of difference test One Way Anova. The results showed F-hit = 3,537> 1,714 or Sig. = 0.006> 0.05, so H0 is rejected. It means that there is an average difference between library users and non-users of the library in connection with their motivation to study. This indicates that motivation to study of students who use library is not the same as that of students who do not use library. It can be concluded that the users of library media have higher learning motivation than the non-users of library media. In other words, students as users of library get motivated more than those as non-users of library.